Thursday
March 30, 2017

Post a New Question

Posted by on .

simplify the expression.

cot^2(x)-csc^2(-x)

  • trig - ,

    csc(-x) = -csc(x)

    sin^2+cos^2 = 1

  • trig - ,

    But my teacher gave the answer on the review as -1.

  • trig - ,

    but but but ... you should have used my hints.

    csc^2(-x) = (-cscx)^2 = csc^2(x)

    sin^2+cos^2 = 1
    divide by sin^2 to get
    1+cot^2 = csc^2
    cot^2 - csc^2 = -1

    sin^2+cos^2=1 will help solve many problems.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question